Evaluating the Effectiveness of Regulatory Frameworks for Transitioning to Net-Zero Energy Buildings in a Tropical Desert Climate - Motaz Mestarehi; Osama Omar (Energies)
Domestic electricity consumption in the Kingdom of Bahrain accounts for 48% of total national electricity consumption, increasing between 1.5 and 3.5% annually. This increase is due to indoor cooling electricity accounting for up to 80% of domestic electricity consumption. The Kingdom is aiming for a reduction in carbon emissions of 30% by 2035 and to achieve carbon neutrality by 2060. Hence, reducing electricity consumption is necessary. Recently, the Kingdom’s Electricity and Water Authority has issued updated building regulations regarding the maximum thermal transmittance allowed for residential buildings. This study employed a quantitative simulation of a typical housing unit (T8) in the Kingdom of Bahrain, assessing building envelope materials and air conditioning efficacy following the updated building regulations via DesignBuilder V. 7.0.2.006 software. Additionally, this study examined the potential of building regulations to facilitate the transition to net-zero energy buildings by comparing electricity consumption with renewable energy generated from rooftop photovoltaic panels. It was determined that electricity consumption could be reduced by up to 52% by following building regulations and relying on current materials in the residential sector. Furthermore, this reduction may facilitate the Kingdom’s attainment of net-zero energy status through onsite power generation of 12,500 kWh/year. This study concluded that achieving net-zero energy status is possible by following building regulations and relying on commercially accessible construction materials; however, guidelines for energy storage or a feed-in tariff for the residential sector must be established.